2022
DOI: 10.1186/s12933-022-01693-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of triglyceride-glucose index with ischemic stroke recurrence in nondiabetic patients with small vessel occlusion: a multicenter hospital-based prospective cohort study

Abstract: Background Triglyceride-glucose (TyG) index is a simple and reliable surrogate marker of insulin resistance. Elevated TyG index was related to stroke recurrence. This study aimed to explore the associations between TyG index with ischemic stroke recurrence in nondiabetic patients with small vessel occlusion. Methods From November 1, 2016 to February 28, 2021, consecutive acute ischemic stroke patients admitted within 1 week after onset were screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In contrast to our initial hypothesis, our findings suggest that there is no significant synergy or interaction between these two factors in their impact on stroke risk. In essence, while both BMI and the TyG independently contribute to stroke risk [ 3 , 4 , 14 , 15 ], their combined effect does not appear to exceed the sum of their individual effects. This observation introduces complexity into our understanding of how BMI and the TyG jointly influence stroke risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our initial hypothesis, our findings suggest that there is no significant synergy or interaction between these two factors in their impact on stroke risk. In essence, while both BMI and the TyG independently contribute to stroke risk [ 3 , 4 , 14 , 15 ], their combined effect does not appear to exceed the sum of their individual effects. This observation introduces complexity into our understanding of how BMI and the TyG jointly influence stroke risk.…”
Section: Discussionmentioning
confidence: 99%
“…Both BMI and TyG are individually associated with stroke [3,4,14,15], in addition, recent studies introduced a novel index called the triglyceride glucose-body mass index (TyG-BMI), and it has also been demonstrated to be associated with stroke [16][17][18]. However, the interplay between these two metrics remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have evaluated the TGI in many areas, including its relationships with acute coronary syndrome in patients without [27][28][29][30][31][32][33] and with type 2 diabetes, [36] body mass index, [34,35] type 2 diabetes, [37][38][39][40][41] ischemic stroke, [41][42][43][44][45][46][47] cardiovascular disorders, [51][52][53] and intravenous thrombosis. [60,61] Like our study, some studies have examined the relationship between TGI and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they concluded that there was a strong relationship between TGI and acute coronary artery diseases. [27][28][29][30][31][32][33] In addition, the relationship between TGI and body mass index has been examined. [34,35] Moreover, TGI values have recently started to attract attention in patients with type 2 diabetes and acute coronary syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were carried out to understand the link between the TyG index and stroke subtypes. Zhang et al reported that the TyG index is correlated with SVD and may have the potential to optimize the risk stratification of SVD 13, 14 . Furthermore, the TyG index was reported to be a useful biomarker of LAA stroke and can help in identifying candidates for carotid reperfusion 15 .…”
Section: Discussionmentioning
confidence: 99%